Pendidikan kebencanaan bagi siswa berkebutuhan khusus - Selvi Afliana Taklal; Elvira Gabriella Ikka; Johanna Ajeng; Evi Deliviana (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
this literature study aims to provide ideas for education in Indonesia in order to build a more quality and equitable education. Indonesia lies in an area prone to natural disasters. Natural disasters are something that cannot be predicted when they occur. Therefore, the Indonesian people need to gain knowledge about disaster mitigation. This can be applied in the field of education, namely with disaster education. Everyone has the right to receive the same education, including students with special needs. Disaster education for students with special needs is very important and serious to be implemented. This is so that they still have enough knowledge to protect themselves from the disaster situation. Disaster education for students with special needs can be done by developing Disaster Preparedness Schools (SSB), simulation training methods in the form of role play, as well as media literacy and disaster interpretation.